The demands of reason : an essay on Pyrrhonian scepticism - Perin, Casey (Oxford : Oxford University Press, 2010)
Casey Perin presents a new interpretation of key ideas and arguments in Sextus Empiricus' 'Outlines of Pyrrhonism', a founding text of the sceptical tradition in philosophy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sextus, -- Empiricus; Reason; Skepticism